A comparison of foot strike events using the force plate and peak impact acceleration measures - Whelan, N.; Healy, R.; Kenny, I.; Harrison, A. J. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
A popular method for measuring initial contact (foot-strike) during running is the force platform. It has been proposed that the foot contact events can be estimated using peak impact related accelerations of the leg using accelerometers. Various studies have been conducted to compare force platform and accelerometer methods in walking and running. The aim of this study was to develop a method for identifying peak impact accelerations in the anterior- posterior axis using the Delsys Trigno System during running and compare this with initial contact via force plates. Seven national and international sprinters completed runs across a force platform with an accelerometer fixed to their shin. The results showed the acceleration of the anterior-posterior axis approximated footstrike within ±0.017 s of the foot-strike event detected by the force plate.